2012
DOI: 10.1007/s00586-012-2585-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of posterior spinal fusion on respiratory function in Duchenne muscular dystrophy

Abstract: Severity of scoliosis was not a key determinant of respiratory dysfunction. Posterior spinal fusion did not reduce the rate of respiratory function decline. These two points suggest that intrinsic respiratory muscle weakness is the main determinant of decline in respiratory function in DMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Although most studies did not mention the detailed radiography data, the mean Cobb angle in the surgical group at the initial consultation in our study (65.5°± 18.7°) was similar to that in other studies (56.4°± 20.7°reported by Alexander et al 6 and >50°, by Kinali et al 4 ); however, the mean Cobb angle in the nonsurgical group in the present study (56.9°± 14.6°) was more severe than that in other studies (34.9°± 26.5°reported by Alexander et al 6 and approximately 50°, by Kinali et al 4 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Although most studies did not mention the detailed radiography data, the mean Cobb angle in the surgical group at the initial consultation in our study (65.5°± 18.7°) was similar to that in other studies (56.4°± 20.7°reported by Alexander et al 6 and >50°, by Kinali et al 4 ); however, the mean Cobb angle in the nonsurgical group in the present study (56.9°± 14.6°) was more severe than that in other studies (34.9°± 26.5°reported by Alexander et al 6 and approximately 50°, by Kinali et al 4 ).…”
Section: Discussionsupporting
confidence: 92%
“…Velasco et al 8 reported that the average rate of decline in forced vital capacity was 4% per year preoperatively, which was reduced to 1.75% per year after surgery. However, other studies 4,6 have not demonstrated any obvious benefits of surgery in terms of respiratory function. The study by Alexander et al 6 had some limitations including the fact that the follow-up period was only one year and the preoperative mean forced vital capacity was significantly lower in the surgical group (36.2%) than in the nonsurgical group (54.3%).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations